2022
DOI: 10.7769/gesec.v13i4.1474
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in courts: Validation of a scale of technological innovation

Abstract: The development of studies on technological innovations in the public sector, specifically in justice system, is still little explored in the literature. This article aimed to develop and validate a scale of technological innovation in the justice system during the period of the COVID-19 pandemic. Data collection procedures were carried out by means of questionnaires sent to 20.727 e-mails of civil servants and judges of the state courts of justice in Brazil. The relationships among the innovation variables th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The results showed that these companies also show little innovative behaviour, which is similarly driven by the lack of employees with technical management knowledge to develop innovative practices. Barbosa, Sousa, Nacife and Novak (2022) provided a different perspective, focusing on validating a scale of technological innovation in the Courts of Justice in Brazil with other innovation approaches. A factor analysis revealed other aspects relevant to promoting organizational learning and innovative practices, such as people's innovative behaviour and organizational resources.…”
Section: Related Studiesmentioning
confidence: 99%
“…The results showed that these companies also show little innovative behaviour, which is similarly driven by the lack of employees with technical management knowledge to develop innovative practices. Barbosa, Sousa, Nacife and Novak (2022) provided a different perspective, focusing on validating a scale of technological innovation in the Courts of Justice in Brazil with other innovation approaches. A factor analysis revealed other aspects relevant to promoting organizational learning and innovative practices, such as people's innovative behaviour and organizational resources.…”
Section: Related Studiesmentioning
confidence: 99%